SISTEM KENDALI ROKET UNTUK GERAK UNPITCHING - Andiarti, Rika; Sofyan, Edi (Indonesian Journal of Aerospace, 2006)
A missile control system utilizing Proportional-Integral-Derivative (PID) controller is proposed. With this controller, the missile is constrained to flight with zero pitch angle. By choosing LAPAN's missile RKX-100 as a dynamic model, this PID controller is applied. Simulation results show that the applying controller seems to be effective in missile unpitching manuver.